2001
DOI: 10.1074/jbc.m100152200
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Integrity Regulates Pak Leading to Ras-independent Activation of Raf-1

Abstract: Growth factors activate Raf-1 by engaging a complex program, which requires Ras binding, membrane recruitment, and phosphorylation of Raf-1. The present study employs the microtubule-depolymerizing drug nocodazole as an alternative approach to explore the mechanisms of Raf activation. Incubation of cells with nocodazole leads to activation of Pak1/2, kinases downstream of small GTPases Rac/Cdc42, which have been previously indicated to phosphorylate Raf-1 Ser 338 . Nocodazole-induced stimulation of Raf-1 is au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 50 publications
2
66
0
Order By: Relevance
“…Western Blot Analysis-Western blot analysis was carried out as described previously (30,31). In brief, HepG2 cells were lysed in buffer (20 mM Tris-HCl, pH 8.0, 1% Nonidet P-40, 1 mM EDTA, 1 mM EGTA, 1 mM sodium orthovanadate, 1 mM dithiothreitol, 1 mM phenylmethylsulfonyl fluoride, 2 g/ml aprotinin, 2 g/ml leupeptin, and 1 g/ml pepstatin).…”
Section: Materials-metforminmentioning
confidence: 99%
See 1 more Smart Citation
“…Western Blot Analysis-Western blot analysis was carried out as described previously (30,31). In brief, HepG2 cells were lysed in buffer (20 mM Tris-HCl, pH 8.0, 1% Nonidet P-40, 1 mM EDTA, 1 mM EGTA, 1 mM sodium orthovanadate, 1 mM dithiothreitol, 1 mM phenylmethylsulfonyl fluoride, 2 g/ml aprotinin, 2 g/ml leupeptin, and 1 g/ml pepstatin).…”
Section: Materials-metforminmentioning
confidence: 99%
“…After fresh serum-free medium was added, cells were treated with metformin (0.5-2 mM) for the indicated times. Preliminary studies revealed that within 48 h of transfection with control Ad-GFP, 80 -90% of HepG2 cells expressed green fluorescent protein.Western Blot Analysis-Western blot analysis was carried out as described previously (30,31). In brief, HepG2 cells were lysed in buffer (20 mM Tris-HCl, pH 8.0, 1% Nonidet P-40, 1 mM EDTA, 1 mM EGTA, 1 mM sodium orthovanadate, 1 mM dithiothreitol, 1 mM phenylmethylsulfonyl fluoride, 2 g/ml aprotinin, 2 g/ml leupeptin, and 1 g/ml pepstatin).…”
mentioning
confidence: 99%
“…We then tested whether the phosphorylation of Ser 445 could be increased by expression of constitutively active Ras or constitutively active PAK1 because Ras stimulates B-Raf activity and because PAK1 phosphorylates Raf-1 at the analogous site (Ser 338 ) (28,36,38,42). The B-Raf N Terminus Contains an Autoinhibitory DomainRaf-1 contains an autoinhibitory domain that minimally encompasses residues 1-147 and that includes the entire RBD and part of the CRD.…”
Section: Regulation Of Phosphorylation Of A-mentioning
confidence: 99%
“…In the present study, the inability of mda-5 to induce apoptosis in CREF-raf cells even after blocking K-ras activity by Ad.Kras(AS) approaches indicates a Ras-independent Raf activation, which was also documented in previous studies. 34,36 However, the susceptibility of CREF-raf to mda-5-induced killing after MEK1/2 inhibition by PD98059 further confirms the involvement of Raf/ MEK/ERK in mda-5-mediated apoptosis. Studies are in progress to analyze the association of Ras/Raf/MEK/ERK pathway with different aspects of the apoptotic machinery involved in Ad.mda-5-induced apoptosis such as bcl-2 family members, as they have been related to Ras/Raf/MEK/ERKmodulated cell survival.…”
Section: Discussionmentioning
confidence: 74%